Genome Editing in Sugarcane: Challenges Ahead - Mohan, Chakravarthi (Frontiers in Plant Science, 2016)
Genome editing opens new and unique opportunities for researchers to enhance crop production. Until 2013, the zinc finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs) were the key tools used for genome editing applications. The advent of RNA-guided engineered nucleases - the type II clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 (CRISPR-associated) system from Streptococcus pyogenes holds great potential since it is simple, effective and more versatile than ZFNs and TALENs. CRISPR/Cas9 system has already been successfully employed in several crop plants. Use of these techniques is in its infant stage in sugarcane. Jung and Altpeter (2016) have reported TALEN mediated approach for the first time to reduce lignin content in sugarcane to make it amenable for biofuel production. This is so far the only report describing genome editing in sugarcane. Large genome size, polyploidy, low transformation efficiency, transgene silencing and lack of high throughput screening techniques are certainly great challenges for genome editing in sugarcane which would be discussed in detail in this review.